Effect of Concentration of Carrageenan and Total Soluble Solid of Immature Apple Fruit Juice on the Quality Aspects of Jelly Candy - Harijono, Harijono; Kusnadi, Joni; Mustikasari, Setyo Ani (Jurnal Teknologi Pertanian, 2001)
The number of fruits in an individual apple tree has to be maintained to a certain level to get optimal development, thus some immature ones are periodically picked up. They are, however, usually treated as a waste and or used as fertilizer. It contained a considerable amount of pectin substances and therefore it is potentially used as raw material for jelly candy. The research was conducted to determine the optimum concentrations of iota-carrageenan and total soluble solid (TSS) of juice of immature apple fruit to make a good quality jelly candy that is accepted by consumers. An experiment type of research was performed employing two factors, the concentrations of iota carrageenan and TSS of apple juice. The first factor, the carrageenan concentration consists of three levels: 0.08%, 0,12% and 0,16%, and the TSS of apple juice of 13 °brix; 19 °brix and 25 °brix respectively. The experiment was carried out in triplicates. The results indicated that a good quality candy jelly may be made from the use of 0.08% iota-carageenan at TST levels of apple juice from 19 to 25 °brix, although the one made with juice of 25 °brix was the most accepted. The characteristics of the best quality product were 18.28% moisture, aw of 0.82,  ph 3.86, reducing sugars content of 24.87%, penetration index of 0,486 mm/g.second, an elasticity index of 0.035 m/n, the degree of lightness (l*) of 40.47, the red hue (a* ) of +5.97 and the yellow hue  (b*) of +36.87 respectively.   Keywords: apple fruit juice, carrageenan, jelly candy